Analysis of flow field in a blast simulator combined-driven by explosive charge and compressed gas - Chen, Zhuo; Ren, Huiqi; Ning, Huijun; Zhou, Songbai; Long, Zhilin; Huang, Kui (Frontiers in Earth Science, 2023)
The flow field characteristics of blast simulators with the explosive-driven method and compression-driven method have been extensively investigated, however, limited effort has been made to the flow field in blast simulators combined driven by explosive charge and compressed gas. In this paper, the finite volume method governed by Navier-Stokes equation based on explosive detonation and k-omega SST turbulence equation was used to analyze the flow field characteristics of blast simulators with three kinds of drive methods, namely, explosive-driven method, compression-driven method, and combined-driven method. The results show that the numerical method could simulate the flow field characteristics of the blast simulators with the explosive-driven method and compression-driven method accurately by comparing to the experimental data, respectively. And the influence of air turbulence on the explosion flow field cannot be neglected in the case of long running time. It is obtained that the combined-driven method could increase the pressure peak value of shock waves and extend positive pressure duration effectively, owing to the interaction of the shock waves generated from the explosive detonation and the rarefaction wave formed by rupturing the diaphragm. The first overpressure peak value, the second overpressure peak value and positive pressure duration obtained by the combined-driven method of 5 kg TNT and 0.3 MPa compressed gas were 1.669 times, 2.172 times and 2.308 times more than those obtained by the explosive-driven method of 5 kg TNT, respectively. The maximum overpressure and positive pressure duration obtained by the combined-driven method of 5 kg TNT and 0.3 MPa compressed gas were 2.56 times and 1.162 times more than those obtained by the compression-driven method of 0.3 MPa compressed gas, respectively. Moreover, various shock wave environments could be simulated by controlling the charge mass of explosive charge and the initial pressure of compressed gas.